What drives consumers in Poland and the Czech Republic when choosing engine oil brand? - Artur Wolak; Kamil Fijorek; Grzegorz Zając; Vojtěch Kumbár (Entrepreneurial Business and Economics Review (EBER), 2019)
Objective: The objective of the research was to study consumer decision-making and purchasing preferences when buying engine oils to reveal the presence of consumer preference heterogeneity. Research Design & Methods: Survey data were collected from Polish and Czech consumers by using a self-administered questionnaire. The main data analysis tools used in the study were the finite mixture models and semantic differential. Findings: Consumers do not constitute a single homogenous group. They cluster into four segments with differing importance profiles. The study found that the largest consumer segment, over one-third of consumers, consider the quality classification, viscosity classification, and OEM specification as the most important criteria during the decision-making process. Implications & Recommendations: As the largest extracted consumer segment includes drivers who are mainly guided by technical specification in the purchasing process, we recommend producers to put additional efforts to provide clearly visible technical specifications on the product label. Contribution & Value Added: The study fills an important gap regarding the lack of empirical research in the context of buying engine oils. The undertaken research indicates that the attention of future consumer research into brand attachment should be shifted from brand loyalty studies towards the study of brand familiarity. The paper presents very valuable model-based consumer segmentation.
Keywords: D12; M31; 330; engine oil; consumer behaviour; choice heterogeneity; consumer segmentation; model-based clustering